KURIKULUM PENDIDIKAN DI JEPANG: PILAR KEBERHASILAN SISTEM PENDIDIKAN DUNIA - Limay Trisno Putra, Ari; Mulyono, Mulyono; Rachmani Dewi, Nuriana (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: This article discusses the distinctive characteristics of Japan's educational curriculum, recognized as one of the most successful education systems in the world. Japan implements a well-structured curriculum through the 6-3-3 education model and the Gakushuu Shidou Youryou national standards, ensuring equitable quality nationwide. The core strength of Japan’s curriculum lies in its holistic Chi-Toku-Tai approach, which balances academic knowledge (Chi), moral character development (Toku), and physical health (Tai). Furthermore, the integrated curriculum approach and project-based learning methods foster student independence, creativity, and essential 21st-century skills. Teacher professionalism is continuously enhanced through collaborative and reflective Lesson Study practices. The success of this system is also supported by the active involvement of families and communities in character education. Despite its achievements, Japan’s education system faces challenges, particularly high academic pressure that may affect students' mental well-being. This study aims to provide valuable insights for other countries, including Indonesia, in designing holistic curriculum policies that balance academic excellence, character formation, and students’ psychological welfare. Keyword: Japanese curriculum, Chi-Toku-Tai, holistic approach, Lesson Study, character education. Abstrak: Artikel ini membahas karakteristik kurikulum pendidikan di Jepang yang diakui sebagai salah satu sistem pendidikan paling berhasil di dunia. Jepang mengembangkan kurikulum yang terstruktur melalui pola pendidikan 6-3-3 dan standar nasional Gakushuu Shidou Youryou yang memastikan pemerataan kualitas di seluruh wilayah. Inti keunggulan kurikulum Jepang terletak pada pendekatan holistik Chi-Toku-Tai yang menyeimbangkan aspek pengetahuan akademik (Chi), pembentukan karakter moral (Toku), dan pengembangan kesehatan fisik (Tai). Selain itu, penerapan pendekatan kurikulum terpadu dan metode pembelajaran berbasis proyek mendorong kemandirian, kreativitas, serta keterampilan abad ke-21 pada siswa. Profesionalisme guru terus ditingkatkan melalui praktik Lesson Study yang kolaboratif dan reflektif. Keberhasilan sistem ini juga didukung oleh keterlibatan aktif keluarga dan komunitas dalam pendidikan karakter. Meskipun demikian, tantangan berupa tekanan akademik yang tinggi tetap menjadi perhatian serius bagi kesejahteraan mental siswa. Pembahasan ini diharapkan dapat menjadi rujukan bagi negara lain, termasuk Indonesia, dalam merancang kebijakan kurikulum yang holistik dan berorientasi pada keseimbangan aspek akademik, karakter, dan kesejahteraan psikologis peserta didik.Kata kunci: kurikulum Jepang, Chi-Toku-Tai, pendekatan holistik, Lesson Study, pendidikan karakter.